2006
DOI: 10.1080/09613210500279596
|View full text |Cite
|
Sign up to set email alerts
|

Indoor environment quality contracts in building projects

Abstract: The scientific literature is replete with examples that indicate that poor indoor conditions at workplaces reduce work performance and increase short-term sick leave. To address good indoor environment quality (IEQ), strategic and practical design decisions are needed in the early phase of the building process to ensure successful implementation. However, current procurement practices are hampered by fragmentation, long subcontract chains and vague performance requirements. A preliminary study is undertaken th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…The contract would include clear sanctions so that those would not raise a debate. The same approach can be used in several different kinds of contracts, such as lease design, pre-lease, pre-financial, purchase and maintenance contracts (Saari and Aalto, 2006). In the case of an office lease contract, the office building lessor gives an indoor condition guarantee to the tenant with a set of target factors that contain clear margins of error (Saari and Tarkki, 2008).…”
Section: The Indoor Environment and Contractingmentioning
confidence: 99%
“…The contract would include clear sanctions so that those would not raise a debate. The same approach can be used in several different kinds of contracts, such as lease design, pre-lease, pre-financial, purchase and maintenance contracts (Saari and Aalto, 2006). In the case of an office lease contract, the office building lessor gives an indoor condition guarantee to the tenant with a set of target factors that contain clear margins of error (Saari and Tarkki, 2008).…”
Section: The Indoor Environment and Contractingmentioning
confidence: 99%
“…The Prime Minister of Finland, Jyrki Katainen, recently stated that mould and indoor climate problems will be the number one issue facing municipalities in the coming years (Finnish Broadcasting Company, 2012). Even without severe indoor climate problems, smaller issues, such as high CO 2 or temperature levels, affect worker effectiveness by 2-8 per cent as well as the amount of sick leaves taken by workers (Federspiel et al, 2002;Saari and Aalto, 2011;Witterseh, 2001). The cost to Finnish society in the form of sick building syndrome, building-related illnesses and diminished worker effectiveness is calculated at €200 per person annually (Saari and Aalto, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Even without severe indoor climate problems, smaller issues, such as high CO 2 or temperature levels, affect worker effectiveness by 2-8 per cent as well as the amount of sick leaves taken by workers (Federspiel et al, 2002;Saari and Aalto, 2011;Witterseh, 2001). The cost to Finnish society in the form of sick building syndrome, building-related illnesses and diminished worker effectiveness is calculated at €200 per person annually (Saari and Aalto, 2011). There are three main reasons for indoor climate problems, excluding pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it also showed that when space use is improved significantly, measures must be taken to guarantee a sufficient level of indoor air quality and climate quality. The results on a case study of Saari and Aalto (2006) research suggest that an improvement in the quality of indoor climate is cost effective when its economic impact on health and productivity are taken into account in addition to the investment, operation, and maintenance costs. The existing quality of indoor climate plays a crucial role in determining the feasibility of raising it.…”
Section: Introductionmentioning
confidence: 99%